INTEGRATION ATN SERVICES ON SATELLITE SYSTEM (Perner's Contacts, 2010)
The satellite component is expected to operate alongside that of the terrestrial component and provide a complementary rather than a competitive service. In this paper, the requirements of inter-working and integration of these networks are discussed at different levels.
Keywords: ATN; satellite system; avionics system